THEORETICAL ANALYSIS OF MOMENT CARRYING CAPACITY OF A REAL-LIFEBEAM MODEL AND ItsHALF SCALE MODEL (International Journal of Engineering and Computer Science, 2022)
This paper focuses on improved physical modeling techniques for small scale reinforced concrete structured subjected to moment represents.Abeam is a component which resist moment that come to the beam directly for any kind of distributed load or imposed point load. In real life it's quite impossible to analyze a beam experimentally before starting construction of a particular structure. It will be easier to check by a small-scale model of that prototype model. After getting a relationship between a prototype model and half scale model, it will be. easier to analyze real life beam model's moment taking capacity only by testing a half scale. model.Assuming a real-life beam model having a length = 10 ft (Simply supported beam) Beam section 12"X14" where width = 12 inch and depth = 14 inch. Support reactions at point A and point B is equal to P/2 kip. For imposed load P kip, maximum bending moment = 2.5P kip-ft. For different values of P, maximum bending moment is different for this particular beam. If P = 10kip, then maximum moment =2.5*10 = 25kip-ft = 300 kip -in Steel ratio: Considering compressive strength of concrete, fc' = 3.5 ksi and Tensile strength of steel, fy = 60ksi. Evaluation of the potential of a real-life beam model at the moment and its half scale model. Another aim is to figure out a relationship between a real-life beam models moment carrying capacity and a half scale model such that it can be conveniently sorted the moment carrying capacity of a real-life beam model by checking the half scale model